Methicillin-Resistant Staphyloccocus Aureus Heel Abscess: An Uncommon Emergency Department Diagnosis - Phelan, Michael P.; Schils, Jean P.; Burval, Daniel; Isada, Carlos M. (The Journal of emergency medicine, 2011)
Heel abscesses present as heel pain that progressively worsens, with associated tenderness and fullness at the heel pad. Radiological studies like computed tomography, magnetic resonance imaging, or ultrasound can help correctly diagnose a heel pad abscess. Generally, these patients require i.v. antibiotics and operative management to adequately drain the abscess. It is recommended to avoid incising the plantar aspect of the heel to minimize chronic post-drainage heel pain.